"It's pretty much flying blind in the home care setting": A qualitative study on the influence of home care specific circumstances on sedation in specialist palliative home care. (January 2023) - Meesters, Sophie; Bazata, Jeremias; Handtke, Violet; Gehrmann, Jan; Kurkowski, Sandra; Klein, Carsten; Bausewein, Claudia; Schildmann, Eva; ,
Background: Existing data on sedation at the end of life indicate challenges in the home care setting, leading to deviations from guidelines or non-provision of sedation. Aim: As part of the "SedPall" study, we aimed to explore circumstances in specialist palliative home care, which influence the practice of sedation. Design: Semi-structured qualitative interviews ( n = 59) and two focus groups ( n = 4, n = 5). Recruitment took place via contact persons. We thematically analyzed the transcripts with the Framework Approach, using MAXQDA 2018.2. Setting/participants: Physicians, nurses, and other members of the multiprofessional team from 10 palliative care units and seven home care teams. Results: Participants reported home care specific circumstances that can be categorized into three interrelated topics. (1) Lack of 24/7 on-site availability, (2) active involvement of the family, (3) challenges regarding teamwork and multidisciplinarity. Participants drew different conclusions from the reported circumstances regarding the feasibility of different types of sedation at home: While some reported to generally use all types of sedation, others stated that some types of sedation are not feasible in home care, for example deep sedation until death. Most participants questioned the applicability of existing sedation guidelines in the home care setting. Conclusion: Our data indicate that sedation practices might currently follow the healthcare professional's attitude or service policy rather than the patient's need. To avoid hospital admission in manageable cases and ensure that home care specific best practice standards are met, existing guideline recommendations have to be adapted and supplemented by additional supporting measures specific for the home care setting.